(untitled) - Maestri, George (Indianapolis, Ind., 2008)
3ds Max At a Glance, a full-color, entry-level book, written by noted industry professional George Maestri, uses a highly visual method to teach basic 3ds Max techniques. Beautiful, crisp layouts visually explain important concepts and Max workflows, and step-by-step tutorials provide hands-on reinforcement. Interface features, menus, key commands, and rendering settings are presented in helpful, economical detail with arrows, diagrams, and targeted explanation. It also includes coverage related to games.
Keywords: Computer animation,Computer graphics,Hoạt hình máy tính,Đồ họa máy tính